Komitmen Organisasi, Akuntabilitas, dan Organization Citizenship Behavior di Institusi Militer - Supeni A Mapuasari; Hadi Mahmudah (President University, 2016)
Organizational citizenship behavior in Military Institution in Indonesia was rarely being evaluated. Thus, the research is aimed to find an empirical evidence supporting the factors affecting organization citizenship behaviour by taking organization commitment as the independent variable and accountabiilty as the intervening variable . One hundred survey questionaires gathered and analized with smartPLS. Organization commitment is proven to have a direct influence toward organization citizenship behaviour, while accountability mediates the direct influence between organization commitment andorganization citizenship behavior. This research enrices literature contribution toward organization citizenship behaviour variable in military aspect.